Implementation and Recruitment Process of Employees at PT PLN (Persero) Riau Region and Riau Islands - Sosiady, Mulia; Ermansyah, Ermansyah (Jurnal Rumpun Ilmu Ekonomi, 2024)
This Research is carried out in the PT. PLN (Persero) Riau Region and Riau Islands, the purpose of this research is to know the process of recruitment of power implemented in the PT. PLN ( Persero ) Riau Region and Riau Islands. Data analysis in this research uses the qualitative descriptive results of the previous discussion, then the author can conclude that in the recruiting process of Power implemented at the level of Senior High School/Vocation Secondary School /level running well and in accordance with the process undertaken by the candidate employees until the employee is accepted as employee of the PT PLN (Persero). However, there are still empty posts in the Human Resource Development Unit section. This means that here there is an Empty post then the job of the post is done by the employees who are in the unit so that will make the achievement of the objectives of the company not achieved well and effectively.